Seeking higher order construction of cognitive abilities in a psychosocial learning environment - Nor Sa’adah Jamaluddin; Rohaila Yusof; Noor Lela Ahmad; Suhaida Abdul Kadir; Arnida Abdullah; Siti Noormi Alias (International Journal of Evaluation and Research in Education (IJERE), 2024)
In this study, we created a psychosocial learning environment consisting of five types of interaction, namely: student collaboration; specific learning objectives and curriculum coherence; learning facilities; independent learning; and constructivist instruction. This research aimed to determine the scope in which the five modes of contact improved students’ learning outcomes in higher order cognitive abilities. This quantitative study involved form four accounting students (N=352) in Malaysia who completed a self-administered questionnaire that included the higher order cognitive abilities (HOCA) test, the instruments of students’ perceived learning environment, and zone-specific demographic data. The results showed two of the five inventory of students’ perceived learning environment (ISPLE) scores. Specific learning objectives and curriculum coherence, were the most significant predictors and strongly correlated with higher order cognitive abilities. Even the components of the psychosocial learning environment impact HOCA in most subjects. However, researchers have obtained new findings that explain other factors that need to be studied to evaluate or encourage HOCA in accounting subjects. Thus, the researcher suggests further research using self-learning methods through modules to assess and promote HOCA in accounting.